STABILITY OF TANKER TRUCKS USING THE DAVIES METHOD - Moreno Contreras, Gonzalo; Flórez Serrano, Elkin; Ramón, Bladimir (Journal of Applied Engineering Science, 2022)
The stability of heavy vehicles is an issue that has been working on in recent times. For this purpose, several models have been developed that allow in a way to determine how prone a vehicle is to rollover. However, most of these models use fixed loads to develop their measurements without including moving loads that in certain cases, decrease the stability of the vehicles. Bearing this in mind, in this article, we propose a two-dimensional kinematic model to determine the Static Rollover Threshold (SRT) using the Davies Method as an analysis tool. Finally, a case study is carried out to determine the influence of the load on the reduction of vehicle stability.
Keywords: tanker trucks, stability, rollover, Davies method